2017
DOI: 10.1089/cell.2017.0020
|View full text |Cite
|
Sign up to set email alerts
|

NRP1 Accelerates Odontoblast Differentiation of Dental Pulp Stem Cells Through Classical Wnt/β-Catenin Signaling

Abstract: Neuropilin-1 (NRP1) is one of the members of neuropilin family. It can combine with disparate ligands involved in regulating cell proliferation, apoptosis, and differentiation. The binding of NRP1 to Sema3A stimulates osteoblast differentiation through the classical Wnt/β-catenin pathway. However, the functions of NRP1 in dental pulp stem cells (DPSCs) are not clear. The aim of our study was to investigate how NRP1 controlled odontoblast differentiation in DPSCs and clarified the underlying mechanisms. NRP1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Meanwhile, more and more researches support that the Wnt/β-catenin signaling pathway regulates stem cell self-renewal, proliferation, and differentiation [2426] and was involved in dental tissue development [2729]. Our previous study found β-catenin was involved in the odontoblast differentiation of DPSCs, too [6]. In this study, the total and nuclear β-catenin protein levels were the highest in the inhibitor group and the lowest in the mimic group, which indicated miR-140-5p was involved in β-catenin activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, more and more researches support that the Wnt/β-catenin signaling pathway regulates stem cell self-renewal, proliferation, and differentiation [2426] and was involved in dental tissue development [2729]. Our previous study found β-catenin was involved in the odontoblast differentiation of DPSCs, too [6]. In this study, the total and nuclear β-catenin protein levels were the highest in the inhibitor group and the lowest in the mimic group, which indicated miR-140-5p was involved in β-catenin activation.…”
Section: Discussionmentioning
confidence: 99%
“…The cell culture process was performed as described in our previous studies [6, 20] and approved by the Ethics Committee of the Affiliated Hospital of Nantong University. Briefly, normal human impacted third molars were collected from patients of 14~22 years of age ( n = 10) after they had given informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Wnt signalling pathway substantially participates in multiple cellular processes, including cell migration, proliferation, and differentiation [14,15]. Canonical Wnt signals are transduced via the intracellular mediator b-catenin.…”
Section: Introductionmentioning
confidence: 99%